Ответ:
Объяснение:
Если нигде не ошибся)))
Автор:
coreyhopkinsⁿ√aᵇ = a^(b/n)
a^n*a^m = a^(m+n)
(a^m)^n = a^(mn)
====================
((a⁴√a + 2⁴√a³)(⁴√a³ + 2⁴√a))² = (( a^5/4 + 2a^3/4)/(a*3/4 + 2a^1/4))^2 =
= (a^3/4*(a^2/4 + 2)/(a^1/4(a^2/4 + 2))^2 = сокращаются a^1/2 + 2 = (a^3/4/a^1/4)^2 = (a*(3/4 - 1/4))^2 = (a^1/2)^2 = a
Автор:
rowanqh1wДобавить свой ответ
Предмет:
Немецкий языкАвтор:
mannОтветов:
Смотреть
Предмет:
ИсторияАвтор:
rolandcalhounОтветов:
Смотреть
Предмет:
Українська моваАвтор:
romeo11Ответов:
Смотреть
Предмет:
Українська літератураАвтор:
peanutОтветов:
Смотреть